2021
DOI: 10.21037/atm-20-6987
|View full text |Cite
|
Sign up to set email alerts
|

Autologous esophageal mucosa with polyglycolic acid transplantation and temporary stent implantation can prevent stenosis after circumferential endoscopic submucosal dissection

Abstract: Background: This research aimed at investigating the safety and efficacy of autologous esophageal mucosa (AEM) with polyglycolic acid (PGA) transplantation and temporary stent implantation (TSI) in preventing esophageal stenosis (ES) after early esophageal cancer (EC) surgery.Methods: Between April 2019 and October 2020, patients scheduled for circumferential endoscopic submucosal dissection (ESD) were prospectively recruited. After ESD, autologous esophageal mucosal patches (MPs) were constructed on the absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Tomonori et al reported a biodegradable esophageal stent for stricture prevention, while the long-term efficacy by 24 weeks was unsatisfactory due to the stricture recurrence as well as the complications such as esophagobronchial fistula [42]. Tissue engineering approaches including the autologous oral cell sheet transplantation, thigh skin-grafting, and cell sheet transplantation were also developed [43][44][45]. The incidence of stricture was reported to be 44% in patients received autologous esophageal mucosa treatment after circumferential ESD [44], but this technology is relatively expensive and laborintensive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tomonori et al reported a biodegradable esophageal stent for stricture prevention, while the long-term efficacy by 24 weeks was unsatisfactory due to the stricture recurrence as well as the complications such as esophagobronchial fistula [42]. Tissue engineering approaches including the autologous oral cell sheet transplantation, thigh skin-grafting, and cell sheet transplantation were also developed [43][44][45]. The incidence of stricture was reported to be 44% in patients received autologous esophageal mucosa treatment after circumferential ESD [44], but this technology is relatively expensive and laborintensive.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue engineering approaches including the autologous oral cell sheet transplantation, thigh skin-grafting, and cell sheet transplantation were also developed [43][44][45]. The incidence of stricture was reported to be 44% in patients received autologous esophageal mucosa treatment after circumferential ESD [44], but this technology is relatively expensive and laborintensive. Autologous skin or esophageal mucosa grafting is an aggressive approach with relatively low patient compliance; recurrent esophageal stricture was found in 8 out of 9 patients (88.9%) during the average follow-up period of 24.7 days.…”
Section: Discussionmentioning
confidence: 99%
“…However, oral cell suspension is less effective for whole circumferential ESD [22,23,25]. In recent years, both domestic and international researchers have attempted to prevent esophageal stricture by autologous mucosal transplantation to alleviate esophageal strictures [19,26,27]. In 2018, autogenous esophageal mucosa transplantation was conducted on nine patients with esophageal cancer who had undergone peri-circumferential ESD.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have focused on extracellular matrix scaffolds, autologous cell suspensions, cell membrane sheets, autologous tissue transplants, etc. [17][18][19]. Autologous epidermal active cell transplantation regeneration technology is a method of transplanting a cell suspension to the wound surface to regenerate the epithelium uniformly and rapidly and avoid scar forma-tion; this approach has been applied in the treatment of burns and skin diseases and has exhibited excellent efficacy [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al . [ 51 ] also reported the application of autologous esophageal mucosa transplantation to prevent esophageal stenosis after circumferential ESD. A total of 25 patients were enrolled and 14 of them did not develop stenosis, which suggested that autologous esophageal mucosa transplantation might be an effective solution to prevent post-ESD stenosis.…”
Section: Autologous Cell Sheetsmentioning
confidence: 99%